Pulse Flour Characteristics from a Wheat Flour Miller's Perspective: A Comprehensive Review. Issue 3 (15th January 2019) - Thakur, S.; Scanlon, M. G.; Tyler, R. T.; Milani, A.; Paliwal, J.
Abstract: Pulses (grain legumes) are increasingly of interest to the food industry as product formulators and consumers seek to exploit their fiber‐rich and protein‐rich reputation in the development of nutritionally attractive new products, particularly in the bakery, gluten‐free, snack, pasta, and noodle categories. The processing of pulses into consistent high‐quality ingredients starts with a well‐defined and controlled milling process. However, in contrast to the extensive body of knowledge on wheat flour milling, the peer‐reviewed literature on pulse flour milling is not as well defined, except for the dehulling process. This review synthesizes information on milling of leguminous commodities such as chickpea (kabuli and desi), lentil (green and red), pea, and bean (adzuki, black, cowpea, kidney, navy, pinto, and mung) from the perspective of a wheat miller to explore the extent to which pulse milling studies have addressed the objectives of wheat flour milling. These objectives are to reduce particle size (so as to facilitate ingredient miscibility), to separate components (so as to improve value and/or functionality), and to effect mechanochemical transformations (for example, to cause starch damage). Current international standards on pulse quality are examined from the perspective of their relationship to the millability of pulses (that is, grain legume properties at mill receival). The effect of pulse flour on the quality of the products they are incorporated in is examined solely from the perspective of flour quality not quantity. Finally, we identify research gaps where critical questions should be answered if pulse milling science and technology are to be established on par with their wheat flour milling counterparts.